LEADERSHIP CONCEPT AT SHARIA BANK; A THEORETICAL STUDY - Havis Aravik; Dwi Sulastyawati; Nur Rohim Yunus (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
The issue of leadership has always been an important and interesting theme to be discussed since it is one of the influencing factors of the success or failure of an organization. Therefore, this article seeks to discuss the sharia bank leadership concept through a theoretical study to provide a clear picture of the leadership concept in sharia banks in theory. This study used library research because all data processed were the library data analyzed with a qualitative-descriptive analysis. The results of this study show that the leadership concept of sharia banks ideally models on the leadership of the Rasulullah (Messenger of Allah) SAW, starting from being smart in communication to being an agent of change, as a coach with the dedication vision and the charismatic spirit.